Preparation method of network structure silicon nitride-based composite material
Patent Information
- Application Number
- CN202410598034.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-15
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-05-15
AI Technical Summary
[0004]本发明提供一种网络结构氮化硅基复合材料的制备方法,优化了陶瓷材料的力学性能与摩擦学性能,解决了现有技术中构建仿生珍珠层结构会降低陶瓷材料的硬度和强度,生产工艺复杂的技术问题
[0021] 1. TiC is selected as the network continuity layer, and its in-situ reaction with Si3N4 is utilized to generate a hard phase TiC. 0.3 N 0.7 This strengthens interfacial bonding and forms a hard network layer to block crack propagation, effectively consuming the energy required for crack propagation and optimizing the fracture toughness of the ceramic while maintaining its high hardness. The combination of Al2O3 and Y2O3, as sintering aids, promotes sintering densification and the phase transformation of β-Si3N4.
Smart Images

Figure CN118666584B_ABST
Abstract
Description
Technical Field
[0001] This invention provides a method for preparing a network-structured silicon nitride-based composite material, which relates to the field of new ceramic materials technology. Background Technology
[0002] With the continuous advancement of science and technology and the increasing demands of industry, the research and application of high-performance structural ceramics has become a hot topic in scientific research and engineering. Silicon nitride (Si3N4), due to its high hardness, high strength, high heat resistance, chemical inertness, and lightweight properties, has shown great potential in aerospace, automotive manufacturing, and mechanical engineering. However, silicon nitride ceramics also exhibit brittleness and poor toughness, making them more easily removed by cutting during friction, resulting in numerous grooves on the sliding surface and ultimately poor tribological properties.
[0003] Introducing a second phase into the silicon nitride structure can improve the poor toughness of silicon nitride-based ceramic materials. With the rapid development of biomimetic engineering, nacreous structures, which primarily construct weak interface layers to induce crack deflection, are increasingly being applied to the ceramics field. However, constructing weak interface layers typically sacrifices the material's hardness and strength, thus limiting the inherent advantages of ceramic materials. Furthermore, complex structural designs mean increased production costs and more stringent requirements for the production environment. Therefore, finding a relatively simple way to prepare advanced structural ceramics with superior performance has become crucial. Summary of the Invention
[0004] This invention provides a method for preparing a network structure silicon nitride-based composite material, which optimizes the mechanical and tribological properties of the ceramic material and solves the technical problems of reducing the hardness and strength of the ceramic material and the complexity of the production process when constructing a biomimetic nacre structure in the prior art.
[0005] This invention is implemented by including the following steps:
[0006] (1) Preparation of spherical silicon nitride powder
[0007] Micron-sized silicon nitride powder is spray-dried to obtain spherical silicon nitride powder, which is then pre-sintered.
[0008] (2) Preparation of network continuous layer slurry and coating
[0009] TiC, Al2O3 and Y2O3 powders with a mass ratio of (5-30):2:3 were wet ball-milled to obtain a network continuous layer mixed powder. 10%-35% of the network continuous layer mixed powder was weighed into a dispersion medium containing a dispersant, and then 65%-90% of the spherical silicon nitride powder obtained in step (1) was slowly added while stirring continuously to obtain a mixed powder slurry with a coating structure.
[0010] (3) Pre-compression and drying
[0011] The mixed powder slurry obtained in step (2) is pre-pressed and dried to obtain a preform;
[0012] (4) High-temperature sintering
[0013] The preform obtained in step (3) is subjected to discharge plasma sintering and then cooled and demolded.
[0014] As a further preferred option, the mass ratio of TiC, Al2O3 and Y2O3 powders is (10-30):2:3.
[0015] As a further preferred option, in step (2), the dispersant is PEG, the amount added is 2-3 drops, the dispersion medium is anhydrous ethanol, and the amount of anhydrous ethanol is 70%-90% of the total mass of the network continuous layer mixed powder and the spherical silicon nitride powder.
[0016] As a further preferred option, the pre-sintering process in step (1) is as follows: pre-sintering temperature 1350℃-1450℃, pre-sintering time 1 hour, and vacuum degree 7Pa.
[0017] As a further preferred option, the drying conditions in step (3) are: drying time of 8h-10h and drying temperature of 50℃-100℃.
[0018] As a further preferred option, the sintering process in step (4) is as follows: pressure 30MPa-40MPa, sintering temperature 1650℃-1700℃, sintering time 10min-15min, sintering atmosphere is nitrogen, and vacuum degree is 0.7KPa.
[0019] As a further preferred option, the median diameter of the spherical silicon nitride powder in step (1) is 75 μm.
[0020] The beneficial effects of this invention are:
[0021] 1. TiC is selected as the network continuity layer, and its in-situ reaction with Si3N4 is utilized to generate a hard phase TiC. 0.3 N 0.7 This strengthens interfacial bonding and forms a hard network layer to block crack propagation, effectively consuming the energy required for crack propagation and optimizing the fracture toughness of the ceramic while maintaining its high hardness. The combination of Al2O3 and Y2O3, as sintering aids, promotes sintering densification and the phase transformation of β-Si3N4.
[0022] 2. The network structure silicon nitride-based composite material prepared by the present invention has excellent anti-friction and wear properties in the room temperature and high temperature range, extending its service life in production or structural components.
[0023] 3. This invention prepares silicon nitride-based composite materials with a network structure in a relatively simple and controllable manner, providing a possibility for the industrial mass production of silicon nitride-based composite materials. Attached Figure Description
[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0025] Figure 1 This is a scanning electron microscope image of the silicon nitride-based composite material with a network structure described in this invention after polishing.
[0026] Figure 2 This is the crack resistance curve of the network structure silicon nitride-based composite material obtained in Example 3 of the present invention.
[0027] Figure 3 This is the crack propagation path of the network structure silicon nitride-based composite material obtained in Example 3 of the present invention.
[0028] Figure 4 and Figure 5 The figures show the changes in friction coefficient and wear rate of the network structure silicon nitride-based composite materials obtained in Examples 1-3 at different temperatures. Detailed Implementation
[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] Example 1
[0031] A method for preparing a network-structured silicon nitride-based composite material includes the following steps:
[0032] (1) The spherical silicon nitride powder (particle size d) obtained by spray drying 50 =75μm), the temperature was rapidly increased from room temperature to 1350℃ and held for 1 hour, with the vacuum degree maintained at 7Pa. After sintering, the furnace was naturally cooled to obtain structurally stable spherical silicon nitride powder.
[0033] (2) TiC (particle size d) was prepared in a mass ratio of 10:2:3. 50 =40nm), Al2O3 (particle size d)50 =0.1μm) and Y2O3 (particle size d) 50 =0.1μm) is added to a ball mill and wet-milled to obtain a network continuous layer mixed powder. 15% of the mixed powder is weighed into a beaker containing anhydrous ethanol and a small amount of dispersant by mass percentage. 85% of the spherical silicon nitride powder obtained in step (1) is slowly added to the mixed slurry by mass percentage, while maintaining stirring, to finally obtain a mixed powder slurry with a coating structure. Among them, the mass of anhydrous ethanol is 70% of the total powder mass, the dispersant is PEG, and the amount added is 2-3 drops. The total powder refers to the network continuous layer mixed powder and the spherical silicon nitride powder.
[0034] (3) The mixed powder slurry with coating structure in step (2) is pre-pressed at a pressure of 14 MPa for 2 min and then dried at 100°C for 8 h to obtain a pre-prepared sample.
[0035] (4) The preform in step (3) is sintered at 1650℃ for 15 min by SPS (spark plasma sintering) at a pressure of 40 MPa. After cooling and demolding, a network structure silicon nitride-based composite material is obtained.
[0036] See Figure 1 Scanning electron microscope (SEM) images of the network-structured silicon nitride-based composite material after sintering and polishing. Testing revealed a material strength of approximately 422 MPa, a hardness of approximately 15 GPa, and a maximum tensile toughness of 5.79 MPa·m. 1 / 2 See also Figure 4 and Figure 5 The coefficient of friction is approximately 0.61 at room temperature and remains stable during the friction process; the coefficient of friction at 800℃ is 0.62.
[0037] Example 2
[0038] A method for preparing a network-structured silicon nitride-based composite material includes the following steps:
[0039] (1) The spherical silicon nitride powder (d) obtained by spray drying 50 =75μm), rapidly heated from room temperature to 1400℃ and held at that temperature for 1 hour, with the vacuum degree maintained at around 7Pa. After sintering, the furnace was allowed to cool naturally to obtain structurally stable spherical silicon nitride powder.
[0040] (2) TiC(d) in a mass ratio of 25:2:3 50 =40nm), Al2O3(d 50 =0.1μm) and Y2O3(d 50=0.1μm) powder is added to a ball mill and wet ball milled to obtain a network continuous layer mixed powder. 30% of the network continuous layer mixed powder is weighed into a beaker containing a certain amount of anhydrous ethanol and a small amount of dispersant by mass percentage. 70% of the spherical silicon nitride powder obtained in step (1) is slowly added to the mixed slurry by mass percentage, while maintaining stirring, to finally obtain a mixed powder slurry with a coating structure; wherein, the mass of anhydrous ethanol is 80% of the total powder mass, the dispersant is PEG, and the amount added is 2-3 drops, and the total powder refers to the network continuous layer mixed powder and the spherical silicon nitride powder.
[0041] (3) The mixed powder slurry with coating structure in step (2) is pre-pressed at a pressure of 14 MPa for 2 min and then dried at 50°C for 10 h to obtain a pre-prepared sample.
[0042] (4) The preform dried in step (3) is sintered at 1700℃ for 10 min by SPS (spark plasma sintering) at a pressure of 30MPa. After cooling and demolding, a network structure silicon nitride-based composite material is obtained.
[0043] The hardness of the network-structured silicon nitride-based composite material obtained in Example 2 was 15.8 GPa, and the maximum tensile toughness was 6.4 MPa·m. 1 / 2 According to the test results, see reference. Figure 4 and Figure 5 The coefficients of friction at room temperature and 800℃ are approximately 0.56 and 0.51, respectively, and the wear rates are approximately 3.23 × 10⁻⁶. -6 and 1.81×10 -6 mm 3 N -1 m -1 .
[0044] Example 3
[0045] A method for preparing a network-structured silicon nitride-based composite material includes the following steps:
[0046] (1) The spherical silicon nitride powder (d) obtained by spray drying 50 =75μm), the temperature was rapidly increased from room temperature to 1450℃ and then held for 1 hour, with the vacuum degree maintained at about 7Pa. After sintering, the furnace was naturally cooled to obtain structurally stable spherical silicon nitride powder.
[0047] (2) TiC(d) in a mass ratio of 30:2:3 50 =40nm), Al2O3(d 50 =0.1μm) and Y2O3(d 50=0.1μm) powder is added to a ball mill and wet ball milled to obtain a network continuous layer mixed powder. 35% of the mixed powder is weighed into a beaker containing a certain amount of anhydrous ethanol and a small amount of dispersant by mass percentage. 65% of the spherical silicon nitride powder obtained in step (1) is slowly added to the mixed slurry by mass percentage, while maintaining stirring, to finally obtain a mixed powder slurry with a coating structure; wherein, the mass of anhydrous ethanol is 90% of the total powder mass, the dispersant is PEG, and the amount added is 2-3 drops, and the total powder refers to the network continuous layer mixed powder and the spherical silicon nitride powder.
[0048] (3) The mixed powder slurry with coating structure in step (2) is pre-pressed at a pressure of about 14 MPa for 2 min and then dried at 50°C for 10 h to obtain a pre-made sample;
[0049] (4) The preform dried in step (3) is sintered at 1700℃ for 10 min by SPS (spark plasma sintering) at a pressure of 30MPa. After cooling and demolding, a network structure silicon nitride-based composite material is obtained.
[0050] The network-structured silicon nitride-based composite material obtained in Example 3 was tested and found to have a hardness of 15.5 GPa and a maximum crack propagation toughness of 10.09 MPa·m. 1 / 2 See Figure 4 and Figure 5 The coefficients of friction at room temperature and 800℃ are approximately 0.65 and 0.68, respectively, and the wear rates are 4.79 × 10⁻⁶. -6 mm 3 N -1 m -1 and 1.51×10 -4 mm 3 N -1 m -1 The thickness of the hard network increases with the increase of TiC content; in this embodiment, the average thickness is approximately 30 micrometers.
[0051] Example 4
[0052] A method for preparing a network-structured silicon nitride-based composite material includes the following steps:
[0053] (1) The spherical silicon nitride powder (d) obtained by spray drying 50 =75μm), the temperature was rapidly increased from room temperature to 1450℃ and then held for 1 hour, with the vacuum degree maintained at about 7Pa. After sintering, the furnace was naturally cooled to obtain structurally stable spherical silicon nitride powder.
[0054] (2) TiC(d) in a mass ratio of 5:2:3 50=40nm), Al2O3(d 50 =0.1μm) and Y2O3(d 50 =0.1μm) powder is added to a ball mill and wet ball milled to obtain a network continuous layer mixed powder. 10% of the mixed powder is weighed into a beaker containing a certain amount of anhydrous ethanol and a small amount of dispersant by mass percentage. 90% of the spherical silicon nitride powder obtained in step (1) is slowly added to the mixed slurry by mass percentage, while maintaining stirring, to finally obtain a mixed powder slurry with a coating structure; wherein, the mass of anhydrous ethanol is 90% of the total powder mass, the dispersant is PEG, and the amount added is 2-3 drops, and the total powder refers to the network continuous layer mixed powder and the spherical silicon nitride powder.
[0055] (3) The mixed powder slurry with coating structure in step (2) is pre-pressed at a pressure of about 14 MPa for 2 min and then dried at 50°C for 10 h to obtain a pre-made sample;
[0056] (4) The preform dried in step (3) is sintered at 1700℃ for 10 min by SPS (spark plasma sintering) at a pressure of 30MPa. After cooling and demolding, a network structure silicon nitride-based composite material is obtained.
[0057] The beneficial effects of this invention are:
[0058] 1. TiC is selected as the network continuity layer, and its in-situ reaction with Si3N4 is utilized to generate a hard phase TiC. 0.3 N 0.7 This strengthens interfacial bonding and forms a hard network layer to block crack propagation, effectively consuming the energy required for crack propagation and optimizing the fracture toughness of the ceramic while maintaining its high hardness. The combination of Al2O3 and Y2O3, as sintering aids, promotes sintering densification and the phase transformation of β-Si3N4.
[0059] 2. The network structure silicon nitride-based composite material prepared by the present invention has excellent anti-friction and wear properties in the room temperature and high temperature range, extending its service life in production or structural components.
[0060] 3. This invention prepares silicon nitride-based composite materials with a network structure in a relatively simple and controllable manner, providing a possibility for the industrial mass production of silicon nitride-based composite materials.
[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a network-structured silicon nitride-based composite material, characterized in that, Includes the following steps: (1) Preparation of spherical silicon nitride powder Micron-sized silicon nitride powder is spray-dried to obtain spherical silicon nitride powder, which is then pre-sintered. (2) Preparation of network continuous layer slurry and coating TiC, Al2O3 and Y2O3 powders with a mass ratio of (5-30):2:3 were wet ball-milled to obtain a network continuous layer mixed powder. 10%-35% of the network continuous layer mixed powder was weighed into a dispersion medium containing a dispersant, and then 65%-90% of the spherical silicon nitride powder obtained in step (1) was slowly added while stirring continuously to obtain a mixed powder slurry with a coating structure. (3) Pre-compression and drying The mixed powder slurry obtained in step (2) is pre-pressed and dried to obtain a preform; (4) High-temperature sintering The preform obtained in step (3) is subjected to discharge plasma sintering and then cooled and demolded.
2. The method for preparing a network structure silicon nitride-based composite material according to claim 1, characterized in that, The mass ratio of TiC, Al2O3 and Y2O3 powders is (10-30):2:
3.
3. The method for preparing a network structure silicon nitride-based composite material according to claim 1, characterized in that, In step (2), the dispersant is PEG, and the amount added is 2-3 drops. The dispersion medium is anhydrous ethanol, and the amount of anhydrous ethanol is 70%-90% of the total mass of the network continuous layer mixed powder and the spherical silicon nitride powder.
4. The method for preparing a network structure silicon nitride-based composite material according to claim 1, characterized in that, The pre-sintering process in step (1) is as follows: pre-sintering temperature 1350℃-1450℃, pre-sintering time 1 hour, vacuum degree 7Pa.
5. The method for preparing a network structure silicon nitride-based composite material according to claim 1, characterized in that, The drying conditions in step (3) are: drying time of 8-10 hours and drying temperature of 50℃-100℃.
6. The method for preparing a network structure silicon nitride-based composite material according to claim 1, characterized in that: The sintering process in step (4) is as follows: sintering pressure 30MPa-40MPa, sintering temperature 1650℃-1700℃, sintering time 10min-15min, sintering atmosphere is nitrogen, and vacuum degree is 0.7KPa.
7. The method for preparing a network structure silicon nitride-based composite material according to claim 1, characterized in that, The median diameter of the spherical silicon nitride powder in step (1) is 75 μm.
Citation Information
Patent Citations
Silicon nitride ceramic substrate and method for manufacturing same
CN114409413A
Silicon nitride / titanium carbide ceramic material preparation method based on spark plasma sintering
WO2022089379A1